Exploratory study on the development of native soil cyanobacteria in the province of Córdoba - Murialdo, R.; Fernández Belmonte, C.; Daga, C.; Gudiño, G.; Pesci, H.; González, C.; Reyna, E. (2024)
Fil: Murialdo, R. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.